Fabrication of coral-like Mn2O3/Fe2O3 nanocomposite for room temperature removal of hydrogen sulfide. Issue 3 (June 2021) - Kim, Suho; Gupta, Nishesh Kumar; Bae, Jiyeol; Kim, Kwang Soo
Abstract: In this study, coral-like Mn2 O3 /Fe2 O3 nanocomposite was synthesized by a surfactant-mediated co-precipitation method. The XRD patterns confirmed the formation of a nanocomposite of Mn2 O3 /Fe2 O3 with no trace of MnFe2 O4 . The surface area of the nanocomposite was 6.18 m 2 g −1 . The metal oxide adsorbents were studied for the adsorptive removal of H2 S gas at ambient conditions. The Mn2 O3 /Fe2 O3 nanocomposite showed the highest adsorption capacity of 11.97 mg g −1 for 0.75 g of adsorbent and 0.2 L min −1 of H2 S flowrate. The XPS analysis confirmed the presence of sulfur majorly in the form of sulfate ions with elemental sulfur and sulfide ions as minor contributors. The XRD pattern showed complete disappearance of Mn2 O3 with the evolution of new peaks for two spinel phases with possible S 2− doping. The study confirmed that the transition metal oxide nanocomposite could be used for removal of H2 S at room temperature. Graphical Abstract: ga1 Highlights: One-step synthesis of coral-like Mn2 O3 /Fe2 O3 nanocomposite. The highest H2 S adsorption capacity of 12.0 mg g −1 at room temperature. XPS analysis confirmed sulfate formation after H2 S adsorption.